Up-Regulation of Endothelin Receptors Induced by Cigarette Smoke — Involvement of MAPK in Vascular and Airway Hyper-Reactivity - Yaping Zhang; Lars Edvinsson; Cang-Bao Xu (The Scientific World Journal)
Cigarette smoke exposure is well known to cause cardiovascular and airway diseases, both of which are leading causes of death and disability in the world. However, the molecular mechanisms that link cigarette smoke to cardiovascular and airway diseases are not fully understood. Vascular and airway hyper-reactivity plays an important role in the pathogenesis of cardiovascular and airway diseases. Recent studies have demonstrated that endothelin receptor up-regulation mediates vascular and airway hyper-reactivity in response to endothelin-1 (ET-1, endothelin receptor agonist) in cardiovascular and airway diseases. In the vasculature and airways, the main functional consequences of up-regulated endothelin receptors by cigarette smoke exposure are enhanced contraction and proliferation of the smooth muscle cells, which subsequently result in abnormal contraction (spasm) and adverse proliferation (remodeling) of the vasculature and airways. The structural alteration by adverse remodeling involves changes in cell growth, cell death, cell migration, and production or degradation of the extracellular matrix. This review focuses on cigarette smoke exposure that induces activation of intracellular mitogen-activated protein kinase (MAPK) and subsequently results in the up-regulation of endothelin receptors in the vasculature and airways, which mediates vascular and airway hyper-reactivity, one of the important pathogenic characteristics of cardiovascular and airway diseases. Understanding the molecular mechanisms of how cigarette smoke causes up-regulation of endothelin receptors in the vasculature and airways may provide new strategies for the treatment of cigarette smoke—associated cardiovascular and lung diseases.